Recovery of copper from industrial sludge as a sustainable resource: A review. Issue 3 (4th July 2022) - Trinh, Ha Bich; Kim, Seunghyun; Son, Taehun; Lee, Jaeryeong
ABSTRACT: The transition from the treatment of the industrial sludge as a solid waste to a potential resource by employing efficient processes is necessary for sustainable development to produce valuable metal such as copper. The recycling of Cu-bearing sludge is thus quite promising as compared to that of mining only primary ores, since it can reduce the energy consumption and environmental impacts due to greenhouse gas emission as well as the depletion of mineral resources. The present review paper emphasizes on the necessity of copper recovery from industrial sludge while examining the compositions and the characterization techniques applied, and current extraction and the separation approaches followed. The most significant issues addressed include the effective extraction of copper and still achieving selective separation from other impurities. The hydrometallurgical techniques provide more appropriate methods for copper recovery from the complex industrial sludge than other approaches; this too requires further investigations to enhance the extraction efficiency, separation selectivity from the leach solutions and the quality of obtained Cu products.